Effect of wearing a face mask on hand-to-face contact by children in a simulated school environment: the Back-to-School COVID-19 Simulation Randomized Clinical Trial - Science, M; Caldeira-Kulbakas, M; Parekh, RS; Maguire, BR; Carroll, S; Anthony, SJ; Bitnun, A; Bourns, LE; Campbell, DM; Cohen, E; Dodds, A; Dubey, V; et al. (American Medical Association, 2022)
Importance Wearing a face mask in school can reduce SARS-CoV-2 transmission but it may also lead to increased hand-to-face contact, which in turn could increase infection risk through self-inoculation.